PPP DAN KEPEMIMPINAN PEREMPUAN (STUDI ATAS PEMENANGAN ADE MUNAWAROH YASIN SEBAGAI BUPATI KABUPATEN BOGOR TAHUN 2018) - Siska Andrianika (Jurnal Adhikari, 2022)
In this modern era, one of the strongest obstacle deterring the emergence of women's leadership are the cultural barriers that connected to cultural norms and even religious norms. In this regard, the succession of women's leadership has become an important agenda in order to create a non-patriarchal government. This research analyzes the leadership of women and Islamic political parties in the success of Ade Munawaroh Yasin becoming a Regent of Bogor Regency in 2018. The purpose of this research is to examine the perspective of the DPC PPP Bogor Regency on women's leadership, especially in the succession of Ade Munawaroh Yasin. The author used a qualitative method followed by a case study examination. The research data collection method was conducted by interview followed by documentation. The theoretical framework and concepts used in this study are the concept of Islamic parties and identity politics, gender and politics and also the concept of women's leadership. The research found that the DPC PPP Bogor Regency PPP no longer had a problem with women's leadership because that matter cannot be separated from the universal value of Islam embraced by PPP. This means that men and women have the same rights to become leaders on a micro and macro scale depend on the level of ability and quality of each individual. Keywords : gender, Islamic parties, leadershipand politics, women.